Rock mass blastability dependence on rock mass quality. - Chatziangelou, M.; Christaras, B. (Bulletin of the Geological Society of Greece, 2013)
The present paper tries to investigate the influence of rock mass quality characteristics on blasting results. In order to come to some conclusions, blastability and quality of rock mass were put together using the already known classification systems. Taking into account the quantity of blastability index (BI) for every possible structural appearance of the poor rock mass, the relation of discontinuities characteristics and blastability index are investigated. The estimations of the above trial gave arise on a new classification system being called “Blastability Quality System (BQS)”, which can be an easily and wide use tool as it is a quickly calculator for blastability index (BI) and rock mass quality.